Multi-authority attribute-based access control system in mHealth with traceability - Qi LI; Hongbo ZHU; Jinbo XIONG; Ruo MO (Tongxin xuebao)
Mobile healthcare (mHealth) is an emerging technology which facilitates the share of personal health records (PHR),however,it also brings the risk of the security and privacy of PHR.Attribute-based encryption (ABE) is regarded as a new cryptology to enhance fine-grained access control over encrypted data.However,existing attribute-based mHealth systems either lack of efficient traceable approach,or support only single authority.A traceable multi-authority attribute-based access control mHealth scheme was proposed,which was constructed over composite order groups and supports any monotonic access structures described by linear secret sharing scheme (LSSS).The adaptive security was proved under subgroup decisional assumptions.The traceability was proved under k-strong Diffie-Hellman (k-SDH) assumption.The performance analysis indicates that the proposed scheme is efficient and available.